STUDY ON THE BIOLOGY OF JOHNIEOPS VOGLERl (SLEEKER) OF BOMBAY WATERS - Muthiah, C (Indian Journal of Fisheries, 2011)
Johnieops vogleri in Bombay waters attains an average size of 158 mm, 240mm and 290 mm at the end of 1, 2 and 3 years as shown by the length-frequencymethod, and 164.4, 220.6 and 276.6 mm as indicated by the scales. The time ofannulus formation in the scales was during May to September which coincideswith low intensity of feeding, spawning activities of the fish and the prevailingmonsoon. Juveniles prefer crustaceans and, as they grow, show the piscivoroustendency. Lower intensity of feeding is noticed during the spawning season. Fiftypercent of the fish mature at 159 mm in length. The relative condition of the fishis correlated to the spawning activities. Fecundity varied from 26,028 to 581,298eggs. The distribution of sexes observed during different months of the year isnot significant except during October and November. Among 130-179 mm sizegroups, males preponderated, whereas females were more among 220-249 mmsize groups.